2006
DOI: 10.1007/s10048-006-0032-6
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analyses reveal molecular relationships among 20 regions of the human CNS

Abstract: Transcriptional profiling was performed to survey the global expression patterns of 20 anatomically distinct sites of the human central nervous system (CNS). Forty-five non-CNS tissues were also profiled to allow for comparative analyses. Using principal component analysis and hierarchical clustering, we were able to show that the expression patterns of the 20 CNS sites profiled were significantly different from all non-CNS tissues and were also similar to one another, indicating an underlying common expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
319
2
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(345 citation statements)
references
References 33 publications
21
319
2
3
Order By: Relevance
“…Transcriptional profiling data from human medulloblastomas was compiled from previously published series (30)(31)(32)(33) and a new series generated at the German Cancer Research Center (Gene Expression Omnibus accession nos. GSE37418, GSE49243, and GSE10327), for a total of 436 medulloblastoma and 18 normal cerebellum samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptional profiling data from human medulloblastomas was compiled from previously published series (30)(31)(32)(33) and a new series generated at the German Cancer Research Center (Gene Expression Omnibus accession nos. GSE37418, GSE49243, and GSE10327), for a total of 436 medulloblastoma and 18 normal cerebellum samples.…”
Section: Methodsmentioning
confidence: 99%
“…We next compiled transcriptional profiles of 436 medulloblastoma and 18 normal cerebellum samples, using a microarray series generated through the PedBrain Tumor Project of the International Cancer Genome Consortium and published microarray datasets (30)(31)(32)(33). The medulloblastoma samples were segregated according to molecular subtypes as described (34,35), which includes tumors associated with WNT pathway activation (group 1), SHH pathway activation (group 2), or more complex etiologies (groups 3 and 4).…”
Section: Significancementioning
confidence: 99%
“…Blood contains organ-specific gene products that are released into circulation through tissue damage, enzymatic cleavage from the cell membrane, or normal blood secretion, providing a source of clinically useful biomarkers for differentiating normal from diseased organs (15). A comparison with published human tissue expression atlases (data on deep comparative transcriptome analyses of multiple organs) (16)(17)(18) showed that 130 of the 320 neuron-specific genes from Cahoy et al (3), of which our 170 genes are a subset, are n = 3 genes*, Accuracy = 80%*** n = 2 genes*, Accuracy = 80%*** n = 3 genes**, Accuracy = 79%*** n = 2 genes**, Accuracy = 76%*** n = 12 genes*, Accuracy = 89%*** n = 6 genes, Accuracy = 74%*** n = 12 genes, Accuracy = 64%*** Gene Ontology gene sets with consistent differences in relative gene expression (reordering of gene set components) between clusters. P values for added-value of GO term vs. random sets of neuron-specific genes (genes, size n), and separability of clusters (accuracy) vs. randomly distributed pixels, calculated by permuting gene and pixel cluster labels, respectively.…”
Section: Transcriptomic Signatures Distinguishing Cortical and Noncormentioning
confidence: 99%
“…We have analyzed the mRNA microarray data, which were generated from 353 human tissue samples [18] and deposited in the databank (Oncomine 4.4; www.oncomine. org).…”
Section: Carma Family Of Scaffold Proteinsmentioning
confidence: 99%